Visible-light enhanced charge storage characteristics of amorphous Ni-doped HfO2 films. (6th July 2018) - Zhang, T; Zhang, Z; Chan, C-H; Li, L T; Wei, M L; Meng, X S; Dai, J Y; Qiu, X Y
Abstract: Photo-induced changes of capacitance–voltage curves for amorphous Ni-doped HfO2 films are probed under different visible light illumination conditions. The illumination-induced minority carriers injection effect enhances the negative shift of flat band voltage, and results in a significant enlargement of memory window. This enlargement exhibits negligible dependence on light wavelength but strong dependence on light intensity in the visible light region. A large memory window width of 6.12 V is obtained under illumination using 650 nm red light with an intensity of 5 mW cm −2 . Acceptable endurance and retention properties show potential applications on new-type photosensitive nano-floating-gate nonvolatile memory devices.